Peran Sosial Guru PAI Dalam Masyarakat Pesisir Pantura Jawa: Studi Kualitatif di Tiga Kabupaten - Nashihin, Muhammad; Kavin Lidinillah, Moh (Darajat: Jurnal Pendidikan Agama Islam, 2022)
This article examines the social role of Islamic Religious Education (PAI) teachers in the northern coastal region (Pantura) of Java, focusing on their contributions outside the classroom. In the context of a pluralistic, religious coastal community that also faces social challenges such as poverty, urbanization, and changing cultural values, PAI teachers emerge as influential agents of change. Using a qualitative-descriptive approach, this study captures how PAI teachers act as educators, community leaders, and socio-religious activists. The study results show that PAI teachers in the Pantura region not only provide formal education, but are also active in da'wah activities, social counseling, and serve as moral and spiritual references in the community. Specifically, five main forms of PAI teachers' social roles were found, namely: (1) serving as a modin (leader) who leads religious rituals such as funerals and wedding prayers; (2) providing religious lectures at community celebrations; (3) serving as a religious consultant who provides Islamic legal and moral advice; (4) being involved in the management of mosques and prayer rooms as preachers, TPA instructors, or religious activity organizers; and (5) active in community organizations such as NU or Muhammadiyah. These findings indicate that the role of Islamic Religious Education teachers is very integral to the social life of coastal communities and is an important element in the stability and strengthening of local religious values. This article recommends the need to strengthen the social and cultural capacity of Islamic Religious Education teachers to be more adaptive to the dynamics of coastal communities.